Demand for Redistribution, Support for the Welfare State, and Party Identification in Austria - Andreas Kuhn (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2009)
This paper describes subjective wage inequality and the demand for redistribution in Austria using individuals' estimates of occupational wages from the International Social Survey Program. Although these estimates differ widely across individuals, the data clearly show that most individuals would like to decrease wage inequality, relative to the level of inequality which they perceive to exist. The empirical analysis also shows that the demand for redistribution is strongly associated not only with variables describing self-interested motives for redistribution, but also with perceptions of and social norms with respect to inequality. Further, the demand for redistribution is a strong predictor for whether an individual is supportive of redistribution by the state. On the other hand, however, I find almost no evidence for an empirical association between the demand for redistribution and individuals' party identification.
Keywords: D31; D63; H50; 330; subjective inequality measures; demand for redistribution; support for the welfare state; party identification